Anticancer Activity of n-Hexane and Acetone Leaf Extracts from Delonix regia (Gul Mohar) on HeLa (Cervical) and Prostate Cell Lines - Saeed Ahmed Sheikh; Asif Ahmed; Asad Ullah; Shazia Nawaz (Journal of Bahria University Medical and Dental College)
Objective: The purpose of this study was evaluation of the anticancer activity of n-hexane and acetone leaf extracts obtained from Delonix regia on BJ, cervical (HeLa), and prostate cell lines.